Chicana in New York City: Gloria Anzaldúa on Spirituality and the City. (17th April 2019) - Alvarado, Li Yun
Abstract: Building on recent Anzaldúa scholarship that foregrounds the importance of spirituality on her poetic and theoretical projects, this article draws attention to an often overlooked period that was critical to Gloria Anzaldúa's spiritual development: 1981-85. During these productive years, she lived on the East Coast, primarily in Brooklyn, and she worked on several projects including portions of her groundbreaking mixed-genre collection Borderlands/La Frontera: The New Mestiza (1987). By examining Anzaldúa's references to New York in archival letters, interviews, prose, and poems, this article sheds light on her personal, poetic, and spiritual development during those East Coast years. In particular, it reads her poems "Antigua, mi diosa" and "Interface" within a New York City context for the first time and outlines the ways in which these poems foreshadow her future theorizations about "nepantla, " "the path of conocimiento, " and "spiritual activism."